Book of Abstracts / 10th International Language Conference on »The Importance of Learning Professional Foreign Languages for Communication between Cultures«, 20 and 21 September 2018, Celje, Slovenia - Marina Bajić; Vičič, Polona; Plos, Alenka (2018)
In today’s highly globalised economy speakers of different languages and respective cultures meet and communicate on a daily basis. Hence, it is of paramount importance that formal education at all levels fosters foreign language skills informed by intercultural competence that today’s students will need when joining the job market and pursuing their professions. To best cater for the needs of students of different professions, language teaching and learning needs to be adapted to the specific needs of individual professions as well as current and emerging trends in language pedagogy. The exploration and dissemination of relevant expertise and good practice in the field of foreign language pedagogy is the main aim of this book, which presents the abstracts of the10th International Language Conference on “The Importance of Learning Professional Foreign Languages for Communication between Cultures” held on 20 and 21 September 2018 at the University of Maribor, Faculty of Logistics.
Keywords: professional foreign languages; foreign languages skills; intercultural competence; specific needs of individual professions; current trends in language pedagogy